Find a Shared Value in the Social Responsibility of Algerian Business Organizations - Mesghouni, Mouna; Youcef, Assma; Kiheli, Aicha Selma; Amani, Lamia; Seddiki, Safia (International Journal of Economics and Financial Issues, 2019)
This study aims to provide a shared value as new business model for Algerian enterprises to create economic values that improve competitiveness of enterprises while creating value for societies. This idea which we see as balancing burdens of social responsibility, placed on those companies on one hand, and guarantees them to maximize the competitive value on the other hand, and this leads us to ask about: the aims of testing the effect of adopting social responsibility in creating shared value. We used simple and multiple regression analysis method to detect the relationship between variables of this study with the optimal model proposal. Data was collected through questionnaire and distributed to a sample of managers and chief executives of economic enterprises who are active in public hygiene. In this study, we find that there is a tendency to adopt social responsibility and statistically significant relationship between social responsibility and shared value Keywords: Social responsibility, shared value, Algeria. JEL Classifications: D21 ; M12; M14 DOI: https://doi.org/10.32479/ijefi.7726